O corpo em cena: escarificações em adolescentes do sexo feminino. - Nascimento, Marina Diniz Luna do (2019)
The scarification in adolescence has gained space and status as a social problem, reaching more and more the reception spaces of psychology, both in the public and private spheres. This study sought to problematize the self-harm in female adolescents, reflecting how the body is used by them. Starting from clinical listening, it was possible to perceive that there is an enigma in the feminine that passes through the body. To encompass this question and to compose the study the theoretical path was traversed, finding subsidies in the Freud-Lacanian psychoanalytic theory and its commentators regarding adolescence, body and feminine. And in order to support the discussions, it was used as a methodology the research in self-mutilation groups on facebook, of these groups were used testimonials and images that subsidized, along with what has remained of the clinical experience, the discussion of the question that guided the work. It was possible to perceive that the scarifications are exits found by the teenagers for what can not be said by the word, the cuts function as an attempt to say the impossible. For those girls there is something that is of the order of the impossible, and which they seem to find singular solutions to this which is unspeakable. After this we perceive that the body is located as an insistence of a letter of jouissance, and in front of it a possible writing is sought. Therefore, it is proposed to think possible alternatives to the new place for the body, having heard in the speeches themselves that both groups of the function and the writing of the impossible also operates in a transformative way.